2012
DOI: 10.1183/09031936.00149011
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin in Pulmonary Arterial Hypertension (APATH) study

Abstract: Statins have been shown to both prevent and attenuate pulmonary hypertension in animal models. This study investigates the potential therapeutic benefits of atorvastatin as an affordable treatment for pulmonary hypertension patients. 220 patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH) were randomised, double-blind, to receive atrovastatin 10 mg daily or matching placebo in addition to supportive care.At 6 months, 6-min walk distance decreased by 16.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 40 publications
0
67
0
Order By: Relevance
“…[24][25][26][27][28] Further, in studies of pleiotropic HMG CoA (3-hydroxy-3-methyl-glutaryl coenzyme A) reductase inhibitor medications ("statins") which, despite effectuating a reduction in "oxidant stress," a reduction in Rho/Rho-kinase (ROCK) signaling, enhanced endothelial nitric oxide production, and increased expression of bone morphogenetic protein receptor type 2, have been disappointing in both the treatment of PAH and experimental models of vascular PGI 2 production. [29][30][31][32][33][34] "Oxidant stress" has been reported in PAH by Cracowski et al, 35 who described increased isoprostane urinary levels that correlated with worsened patient survival. Further, using oligonucleotide microarray gene expression, Geraci et al 36 have described an increase in pulmonary expression of oxidative genes in PAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Further, in studies of pleiotropic HMG CoA (3-hydroxy-3-methyl-glutaryl coenzyme A) reductase inhibitor medications ("statins") which, despite effectuating a reduction in "oxidant stress," a reduction in Rho/Rho-kinase (ROCK) signaling, enhanced endothelial nitric oxide production, and increased expression of bone morphogenetic protein receptor type 2, have been disappointing in both the treatment of PAH and experimental models of vascular PGI 2 production. [29][30][31][32][33][34] "Oxidant stress" has been reported in PAH by Cracowski et al, 35 who described increased isoprostane urinary levels that correlated with worsened patient survival. Further, using oligonucleotide microarray gene expression, Geraci et al 36 have described an increase in pulmonary expression of oxidative genes in PAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most investigated and consistent has been simvastatin, which in doses of 2 to 20mg/kg daily not only prevented but also consistently reversed pulmonary hypertension in animal models. Studies on human cells in culture demonstrated inhibition of vascular smooth muscle and fibroblast proliferation, providing further confidence of a direct anti-vascular remodeling effect but subsequent studies in PAH patients have failed to demonstrate a clear benefit (Kawut, Bagiella, Lederer, & Shimbo, 2011;Wilkins, Ali, Bradlow, & Wharton, 2010;Zeng et al, 2012). Simvastatin 40 to 80mg daily, the higher end of the dose range used for cholesterol reduction, reduced right ventricular mass transiently over 6 months but had no significant effect on 6 minute walk distance (Kawut et al, 2011;Wilkins et al, 2010).…”
Section: Statinsmentioning
confidence: 99%
“…Nevertheless, recent clinical trials demonstrate only transient efficacy when phosphodiesterase type 5 inhibitor and/or endothelin receptor antagonist were supplemented by statins in PH (18). Such disappointing results have raised i.e., the question of whether particular statins at particular doses or regimens will be effective rather than all statins (18,20). The time when statin is added to PH conventional therapy might also influence its efficacy.…”
Section: Biochemical Parametersmentioning
confidence: 99%